SILENCE SPEAKS: THE POLITENESS OF BEING SILENT IN REFUSAL AMONG BUGINESE PEOPLE - Muhayyang, Maemuna; Armas, Muh.Fakhrul; Syamsuri, Andi Sukri; Putri, Andi Siti Nurhasanah Navilah; Amiruddin, Achmad Fauzi; Ruhwana, A. Isma (Universitas Muhammadiyah Lampung, 2026)
This study investigates the use of silence as a politeness strategy in the speech act of refusal among native Buginese speakers. While often regarded merely as the absence of speech, silence in the Buginese context serves significant pragmatic functions. The research aims to identify the various forms of silence, its role as a politeness strategy, the influence of the cultural value of Siri’, and the social contexts that shape its use. A descriptive qualitative approach was employed, with data collected through in-depth interviews with Buginese participants. The findings reveal that silence in Buginese refusals is multimodal, expressed through nonverbal cues such as lowered gaze, faint smiling, and delayed verbal responses. Functionally, silence acts as a face-saving strategy that helps to mitigate conflict and preserve interpersonal harmony. The study further highlights that this practice is deeply intertwined with the cultural value of Siri’ (dignity/shame), that speakers choose silence to avoid causing embarrassment to the interlocutor. This strategy is most commonly employed in hierarchical settings, especially when engaging with elders or respected figures. The study concludes that silence is a purposeful communicative competence that reflects the local wisdom and social ethics of Buginese society